Memodifikasi Sistem Pendidikan di Sekolah Menengah dengan Pemberdayaan Media Digital dan Keterampilan Informasi dalam Kurikulum Merdeka - Andi Setiawan (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to analyse the impact of modifications to the education system at Vocational School Darussalam Banyuwangi through empowering digital media and information skills in the Merdeka Curriculum. The main aim of this research is to analyse how digital media integration affects teaching methods, curriculum, and educational outcomes, as well as assess students' readiness to face future challenges. The research method used is a qualitative approach with a case study design. Data was collected through in-depth interviews with school principals, teachers, and students, classroom observations to observe the implementation of digital media in the learning process, and analysis of curriculum documents and teaching materials. Data analysis was carried out using thematic analysis techniques to identify main patterns and themes from interviews, observations, and documents. The research results show that integrating digital media into the Merdeka Curriculum has improved teaching methods by increasing interactivity and student involvement. In addition, empowering information skills helps students manage and utilize information sources effectively. Although there are challenges to implementation, such as the need for additional training for teachers and technical issues, this research identifies strategies that can overcome these obstacles and increase the effectiveness of the curriculum. This research provides valuable insight into the adaptation of the education system in the digital era and offers recommendations for improving the implementation of the Merdeka Curriculum in secondary schools.